Hydrogeological characterisation and groundwater exploration for the development of irrigated agriculture in the West Kimberley region, Western Australia - Gallardo, Adrian Hugo (2019)
This work presents findings from an exploration programme aimed at identifying new sources of groundwater for irrigated agriculture in the West Kimberley region of Western Australia. The investigation combined drilling, geophysics, hydraulic tests, and water-quality data to improve the understanding of the aquifers’ system. Geologically, the area was interpreted as part of an asymmetric syncline trending northwest towards the coast. Fractures and lineaments are largely concealed but they might disrupt the continuity of the aquifers at certain locations. Groundwater lies primarily in Mesozoic sediments of the Wallal Sandstone, and in the lower section of the Erskine Sandstone underneath. Pollen analysis casts doubt on the age of the Wallal Sandstone, which could actually correspond to a sequence not previously recognised in the area. Concentrations of major ions indicate that for the most part, waters are fresh and suitable for irrigation. The most productive zone for water abstraction locates in western outcrops of the Wallal Sandstone, where bore yields exceed 60 L/s. The northern flank of the syncline is also favourable for pumping the Erskine Sandstone although, fine-grained sediments make the aquifer less productive. The main source of groundwater recharge is rainwater. Chloride concentrations suggest that groundwater replenishment would range between 1% and 3% of the average annual rainfall. The safe yield has been estimated at 4.5 GL/year and 8.7 GL/year for the Wallal and Erskine aquifers respectively. Though several uncertainties remain to be addressed, the study contributes to future planning and a sustainable use of the groundwater resource.